The Dual Role of Hypoxia-Inducible Factor-1α in Sepsis-Induced Immunomodulation and Organ Dysfunction: A Systematic Review and Meta-Analysis - Hudari, Harun; Mega Permata; Ratna Maila Dewi Anggraini; Raden Ayu Linda Andriani (HM Publisher, 2025)
Background: Sepsis, a life-threatening organ dysfunction caused by a dysregulated host response to infection, remains a leading cause of global mortality. Hypoxia-inducible factor-1α (HIF-1α) is a master transcriptional regulator of the cellular adaptive response to hypoxia but plays a complex, paradoxical role in sepsis. While essential for innate immune function, its sustained activation may amplify inflammation and drive organ damage. This meta-analysis was conducted to synthesize the evidence on the association of HIF-1α with key markers of immunomodulation and organ dysfunction in sepsis. Methods: We performed a systematic review and meta-analysis following PRISMA guidelines. A comprehensive search of PubMed, Scopus, and Web of Science was conducted for studies published between January 2014 and December 2024. We included observational studies that measured HIF-1α levels in adult sepsis patients and reported outcomes related to organ dysfunction (Sequential Organ Failure Assessment [SOFA] score) or mortality, and immunomodulation (Interleukin-6 [IL-6] levels). Seven studies meeting the inclusion criteria were included in the final analysis. Data were pooled using a random-effects model. Standardized Mean Difference (SMD) and Odds Ratios (OR) with 95% confidence intervals (CI) were calculated. Results: The seven included studies comprised 1,288 patients. The overall quality of the included studies was moderate to high as per the Newcastle-Ottawa Scale. The pooled analysis revealed that HIF-1α levels were significantly elevated in sepsis patients who died compared to those who survived (OR = 2.68, 95% CI: 1.55–4.64, p < 0.001), with moderate heterogeneity (I² = 45%). Furthermore, HIF-1α levels were strongly associated with greater organ dysfunction, as measured by the SOFA score (5 studies; SMD = 0.92, 95% CI: 0.51–1.33, p < 0.0001), with substantial heterogeneity (I² = 78%). HIF-1α levels also showed a significant positive correlation with the pro-inflammatory cytokine IL-6 (4 studies; SMD = 1.15, 95% CI: 0.65–1.65, p < 0.00001), with high heterogeneity (I² = 82%). Conclusion: This meta-analysis provides robust evidence that elevated HIF-1α levels are significantly associated with increased sepsis severity, characterized by greater organ dysfunction, a heightened pro-inflammatory state, and a higher risk of mortality. These findings underscore the maladaptive consequences of sustained HIF-1α activation in sepsis, positioning it as a critical prognostic biomarker and a complex, high-value target for future therapeutic modulation.